Socio-economic impacts under different sea-level rise scenarios: analysis at local level along the coastal area of Rome (Italy) - Montanari, Armando; Deravignone, Luca; Staniscia, Barbara (Italian journal of engineering geology and environment, 2016)
<span data-sheets-value="{"1":2,"2":"Sea-level rise (SLR) is often associated with climate change and human action in modifying nature and the environment. The research presented in this paper concerns the effects and impacts of different SLR hypotheses in Italy, along the Rome coastal area, in the Ostia district. The study was carried out at the local level, using micro-spatial data, in the context of the European Union’s Seventh Framework Programme (FP7) project SECOA – Solutions for Environmental Contrasts in Coastal Areas; its aim is to offer local policy makers a tool to support and facilitate their decision-making processes. Effects and impacts are analysed and presented for two alternative SLR scenarios. The first one follows the hypotheses made by the Intergovernmental Panel on Climate Change (IPCC), the second one those made by Rahmstorf, in 2007. The two scenarios consider a SLR of 0.2-0.6 m and 1.00-1.40 m, respectively, by the year 2100. The coastal surface area flooded in the IPCC scenario equates to ca. 876 m2, while the flooding in the Rahmstorf scenario totalled ca. 690,322 m2. Damages in terms of loss of land with different uses, loss of dwellings, loss of jobs, need for a relocation of resident population are the most\rsevere estimated impacts of that extreme event of the Rahmstorf scenario."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">Sea-level rise (SLR) is often associated with climate change and human action in modifying nature and the environment. The research presented in this paper concerns the effects and impacts of different SLR hypotheses in Italy, along the Rome coastal area, in the Ostia district. The study was carried out at the local level, using micro-spatial data, in the context of the European Union’s Seventh Framework Programme (FP7) project SECOA – Solutions for Environmental Contrasts in Coastal Areas; its aim is to offer local policy makers a tool to support and facilitate their decision-making processes. Effects and impacts are analysed and presented for two alternative SLR scenarios. The first one follows the hypotheses made by the Intergovernmental Panel on Climate Change (IPCC), the second one those made by Rahmstorf, in 2007. The two scenarios consider a SLR of 0.2-0.6 m and 1.00-1.40 m, respectively, by the year 2100. The coastal surface area flooded in the IPCC scenario equates to ca. 876 m2, while the flooding in the Rahmstorf scenario totalled ca. 690,322 m2. Damages in terms of loss of land with different uses, loss of dwellings, loss of jobs, need for a relocation of resident population are the most severe estimated impacts of that extreme event of the Rahmstorf scenario.